Didactic proposal for the development of leadership skills in parataxonomists (Biocenosis, 2024)
The writing presents a didactic proposal for the development of leadership skills in parataxonomists to optimize the personal and professional performance of this population; in this regard, it is important to point out that the improvement of the work of collaborators is crucial in times when organizations, including environmental organizations, are immersed in constant changes. For this reason, the development of skills such as communication, collaboration, digital literacy and leadership, can be an opportunity for the same staff to have the resilient conditions to creatively face the challenges that arise, since the lack of development of these skills could lead to poor performance of parataxonomists, affecting the ability to contribute effectively to the objectives and sustainability of their organizations, which in turn could have a direct impact on the effectiveness of conservation efforts and sustainable management of natural resources. In this case, four workshops were designed, each one related to the above-mentioned skills, in which a didactic strategy is presented that promotes or strengthens these skills. It is concluded that the didactic proposal represents a valuable and structured strategy for the personal and professional development of parataxonomic personnel, with the potential to significantly improve organizational effectiveness and the conservation of biodiversity from the work carried out by the target population.
Keywords: leadership; training program; organizational sustainability; biodiversity conservation; parataxonomist